Inovação em organizações públicas brasileiras: análise de práticas organizacionais relacionadas às competências coletivas - Lins, Carolina Teixeira de Miranda (2023)
Public organizations have been progressively adopting innovation in order to face challenges and provide citizens with better quality and efficient services. To achieve this, it is essential to develop skills focused on innovation. This research was based on a multi-level skills model, proposed by Montezano (2021) and analyzed teams that won awards in the Public Sector Innovation Competition, promoted by Enap. It sought to verify collective competencies and identify organizational practices aimed at innovation and that were related to those. In this context, the research used a qualitative approach, in a multiple case study, with triangulation of data obtained in 14 interviews and 19 reports from the award-winning teams. As results, the 18 collective competencies validated by Montezano (2021) were observed and identified as related organizational practices: encouraging innovation, organizational support, establishing partnerships, formal and informal networks, as well as carrying out training and qualifications . In view of this, it is expected to contribute to actions to develop and strengthen organizational practices and collective skills that are fundamental for innovative actions, enabling improvements in work processes and the provision of more efficient and effective public services to society.